The Effect of the 4p’s Of Electronic Cigarettes Towards Customer Satisfaction and Customer Loyalty in Indonesia - widhi jati kusumah; ra afera ratna wijayanti (IULI Publisher, 2023)
As the world becomes more environmentally concerned, people are rapidly shifting from conventional (things) to cleaner energy, especially electric-based power. This is reflected in the increasing interest and shares of electric cars and motorcycles alike. The cigarette market has also seen a decline ever since the rise of electronic cigarettes. While electronic cigarettes can be seen as a better and cheaper alternative for the long run, its function remains the same as its conventional tobacco counterparts. The phenomena and the general statement of the problem that has always surrounded the tobacco and nicotine industry is that when consumers spend money, it is expected that it is spent on something beneficial for both the short and the long term. However, tobacco and nicotine companies have marketed their products in such a way that it has become a want or even a need for individuals on a daily basis, and as such, acts as the catalyst of this study. This study was conducted through the distribution of questionnaires, and collected a total of 100 respondents. All data collected were then analyzed using the statistics tool of SPSS version 26, which is further processed by using a path analysis by Structural Equation Modelling in AMOS version 23. The results of this study found out that Marketing Mix significantly affects Customer Satisfaction, Marketing Mix does not significantly affect Customer Loyalty, and Customer Satisfaction does not significantly affect Customer Loyalty. With these results, vape companies should continue to utilize the Marketing Mix and maximizing them to their full potential, though some careful considerations have to be made, such as the target market’s budget, the desired profit margin, pricing strategies, and the pricing and the operations of competitors, which could affect both Customer Satisfaction and Customer Loyalty. Keywords: E-cigs, Electronic Cigarettes, Price, Promotion, Place, Product, Customer Satisfaction, Customer Loyalty